57‐1: Invited Paper: Ink‐Jet‐Printed OLED Displays. Issue 1 (May 2017) - Böhm, Edgar; Levermore, Peter; Tseng, Hsin-Rong; Bealle, Gaelle; Wang, Hsing-Ju; Hibon, Pauline; Heil, Holger; Jatsch, Anja; Buchholz, Herwig
Abstract : We report the performance of inkjet printed red, green and blue OLEDs, with focus on transition from evaporated blue common layer to printed blue panel design. Printed OLED device efficiencies and colors are reported, and we demonstrate that in these metrics, printed red, green and blue OLEDs are now comparable to state‐of‐the‐art vapor‐processed devices.